UMTS Core Network Simulator / Too Sea Chen - Too, Sea Chen (2003)
The wireless industry continues to offer new opportunities and challenges: The rise of wireless devices, plus the rising bandwidth requirements envisioned the potential packet data applications, is creating a huge collection of attempt to shore up that goal. IMT2000 specification has some platforms all called 3G, and since they meet up particular data throughput necessities, the decisions are enormous and vital for an operator to put together. The UMTS development has introduces an all-IP multimedia network architecture. This step in the evolution represents a transform in the general call model. Particularly, both voice and data are mostly handled in the same method all the way from user terminal to the final destination. This architecture can be considered the essential convergence of voice and data. The aim of this thesis report is to develop a UMTS Core Network simulator based on 3GPP Release 5 All-IP Network Architecture. It can offer a means for researches and network planners to analyze the behavior of UMTS Core Network without the expense of building a real network. An main feature of this simulator is multithreading, that support concurrent processing. More than one process can be executed at the same time. Hence, an object-oriented programming approach had been choose to implement it.